Trees, Woods and Forests : a Social and Cultural History. - Watkins, Charles (Reaktion Books, 2014)
Forests-and the trees within them-have always been a central resource for the development of technology, culture, and the expansion of humans as a species. Examining and challenging our historical and modern attitudes toward wooded environments, this engaging book explores how our understanding of forests has transformed in recent years and how it fits in our continuing anxiety about our impact on the natural world. Drawing on the most recent work of historians, ecologist geographers, botanists, and forestry professionals, Charles Watkins reveals how established ideas about trees-s.